(3Gdefgd GdUGaj hGdeSJhaj HYO GdhGajs - (3jhSa Hf JZQj HQOj Hf YHO Gddg GdXGgQj GdMfaj, CHh GdeMGSf , GHf JZQj HQOj , LeGd GdOjf, J (B874 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eOHQ GdOghQ heOhQ GdCYeGQ hGdTghQ s
(3hgh jTJed Ydi JQGLe GdYdeGA hGdCYjGfs
(3eQJH Ydi MQha GdeYLes
(3HOCg ef SfI (B650(3g` ef ChGFd GdOhdI GdJQcjI ef GdeYR CjHc GdJQceGfi Edi Ref GdeDdas
(3SJI CLRGA s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs